Monstrous nights - Dimova, Genoveva (Dimova, Genoveva. Witch's compendium of monsters, 2024)
"With her magic reclaimed and her role in the community of Chernograd restored, Kosara's life should finally be back to normal--but, of course, things can't possibly be that simple. She is now in possession of twelve witch's shadows, which belonged to a series of young, magically powerful women lured into the deadly marriage with the Zmey that Kosara only narrowly escaped as a young woman. Holding them may grant her unprecedented power, but that doesn't mean they're always willing to do her bidding. Across the wall in Belograd, Asen chases the only lead on his latest case, one of several unsolved witch murders, even against the orders of his direct superior and the mayor. He's convinced the smuggling kingpin Konstantin Karaivanov is behind them, and follows his trail to an underground monster auction--which leads him right back to Chernograd. There, sinister events follow one after another: snow falls in midsummer, a witch with two shadows is found dead, monsters that should only appear during the Foul Days have been sighted, and cracks appear in the sky that only Kosara seems able to see. The barrier between worlds thins ... and Kosara can't help but feel her actions are the cause"--